An Issue in the Martingale Analysis of the Influence Maximization Algorithm IMM - Chen, Wei (Proceedings of the 7th International Conference on Computational Social Networks (CSoNet'2018), 2018)
This paper explains a subtle issue in the martingale analysis of the IMM algorithm, a state-of-the-art influence maximization algorithm. Two workarounds are proposed to fix the issue, both requiring minor changes on the algorithm and incurring a slight penalty on the running time of the algorithm.